2019
DOI: 10.1039/c9gc02274k
|View full text |Cite
|
Sign up to set email alerts
|

Microbial production of sebacic acid from a renewable source: production, purification, and polymerization

Abstract: Sebacic acid is an aliphatic ten-carbon dicarboxylic acid (1,10-decanedioic acid) with a variety of industrial applications. Here, we present its microbial production, purification, and polymerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Mono- and polycarboxylic acids (mono- and poly-CAs) are ubiquitous in nature and represent a large repository of platform chemical precursors . Several reports have shown that CAs can be derived from biomass-based resources such as lignin and hemicellulose using green and economically feasible methods. , Likewise, many different methods for producing dicarboxylic acids (di-CAs) from biomass have been developed. Although the produced CAs are valuable by themselves, their corresponding terminal alcohols (ALs) are more interesting as platform chemicals, as they may find useful applications in the production of polymers and as fuel additives to improve the octane number. Moreover, terminal ALs are in general synthetically more useful than the parent CAs.…”
Section: Introductionmentioning
confidence: 99%
“…Mono- and polycarboxylic acids (mono- and poly-CAs) are ubiquitous in nature and represent a large repository of platform chemical precursors . Several reports have shown that CAs can be derived from biomass-based resources such as lignin and hemicellulose using green and economically feasible methods. , Likewise, many different methods for producing dicarboxylic acids (di-CAs) from biomass have been developed. Although the produced CAs are valuable by themselves, their corresponding terminal alcohols (ALs) are more interesting as platform chemicals, as they may find useful applications in the production of polymers and as fuel additives to improve the octane number. Moreover, terminal ALs are in general synthetically more useful than the parent CAs.…”
Section: Introductionmentioning
confidence: 99%
“…Integration of the β-oxidation degradation pathway with the ω-oxidation pathway offers an efficient strategy for generating high yields of MCFAs-derived compounds. Compared with previously reported MCDCAs biosynthetic pathways, such as the reverse β-oxidation pathway, ω-oxidation pathway, and LCFAs oxidation cleavage pathway, , this proof-of-principle route enjoys numerous advantages for producing the desired chemicals. Unlike glucose metabolism, FA catabolism generates directly the target products and acetyl-CoA for cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…Another promising candidate for improving the flexibility and toughness of PLA may be poly(butylene sebacate) (PBSe), a bio-based and biodegradable aliphatic polyester that can be synthesized by the polycondensation of sebacic acid (Se) with 1,4-butanediol (BDO) [ 43 ]. The bio-based character of PBSe comes from the fact that both of its precursor monomers can be obtained from renewable sources, Se being produced by the alkaline pyrolysis of castor oil [ 44 ] and BDO being obtainable via the microbial fermentation of sugars from renewable sources [ 45 ]. Similar to PLA, PBSe is a biodegradable polymer in composting conditions [ 46 ].…”
Section: Introductionmentioning
confidence: 99%